현대 앱아트의 표현 유형 분류 - 앱의 활용에 의한 결과물을 중심으로 - 하임성; Ha Im Sung (기초조형학연구, 2019)
그동안의 모바일아트에 대한 연구들은 주로 인터랙티브 미디어아트, 증강현실 미술 내에서 간헐적으로, 혹은 포괄적인 맥락에서 다루어져 왔고, 최근 표출되고 있는 다양한 특성들을 밀도 있게 분석한 연구는 국내외적으로 많지 않다. 본 연구의 목표는 2008년 이후부터 지금까지 전 세계에서 제작되고 있는 ‘앱이 활용되는 모바일아트’ 작품 사례들의 표현유형을 ‘앱의 활용에 의한 결과물을 중심으로’ 세분화하고 의의를 고찰하는 것이다. 연구의 방법 및 과정은 다양한 자료 수집을 통해 전 세계 앱아트 작품 사례 106개를 수집한 후, 유형별 분류를 하고 이를 여러 담론들 및 선행 장르들과 비교분석하였다. 이를 통해 앱의 활용에 의한 결과물을 중심으로 현대 앱아트의 표현 유형을 ‘증강현실’, ‘타 주체와 네트워크 내상호작용 과정’, ‘작가가 제작한 고정적 콘텐츠’, ‘타 작품 정보들’ 이라는 네 가지 항목으로 분류할 수 있었고, 그 분포 및 의미는 다음과 같다. 앱 내에서 증강현실을 구현하는 작품은 약 69%로 대다수를 차지하고 있었고, ‘체험적인 일시적 현존, 증강현실에 내재된 장소특정성, 현대 사회의 표상’이라는 의미를 내재하고 있었으며 일부 미니멀리즘 미술, 대지미술 등과의 속성이 유사하였다. ‘타 주체와의 네트워크 내 상호작용 과정’은 약 20% 였으며 기계나 다양한 주체와의 소통과정, 그 결과물을 작품으로 승화하고 있었고 현대 참여미술 내 장르들과 궤를 함께 하고 있었다. ‘작가가 제작한 고정적 콘텐츠’ 영역은 약 7.5%였고 앱으로 평면이나 동영상 콘텐츠를 전달하고 있었다. ‘타 작품 정보들’은 약 3.8%로써 앱으로 스캔하는 대상을 다른 작품정보와 연결시키고 있었으며 과거 웹아트의 형식과 유사하였다. 그러므로 현대 앱아트에서 생산되는 결과물은 ’증강현실‘이 가장 많았으며, 이것은 여타 디지털아트 내 장르들 중에서 잘 표출되지 않는 앱아트만의 가장 두드러지는 표현유형이었고, 그 의의에 대한 다양하고 심도 깊은 후속 논의는 지속될 것이다. 그리고 본 연구를 통해 아직 미지의 세계인 현대 앱아트 연구의 폭을 확대할 수 있었다. To date, research on mobile art has been mainly dealt in intermittent or comprehensive context within interactive media art and augmented reality art. And only a few domestic and overseas studies intensively looked into a variety of the characteristics that have been recently expressed. The purpose of this study is to break down and investigate the expressional topology of mobile artworks using apps in the world, focusing on the results of using the apps. To achieve the purpose, I collected 106 app artworks throughout the world for data connection, classified their types, and compared and analyzed them with several discourses and previous genres. As a result, I was able to break down the types of the modern app art expressions into ‘AR', ‘interaction process with other subjects in a network', ‘fixed contents sphere created by an author', and 'other work information'. They are distributed and have significance as follows. The majority (about 69%) of the mobile app artworks realize AR inside an application, featuring 'experimental and temporary existence', 'place specificity inherent in AR', and 'symbol of the modern society’. In some parts, they are similar to the attributes of minimalism art, land art, etc. 'Interaction process with other subjects in a network’ achieved about 20%. This type of expression communicates with a machine or other subjects, sublimates the results into artworks, and has the same way as other genres of the modern participatory arts. ‘Fixed contents sphere created by an author' took about 7.5%. Plane or video contents are delivered with an application. 'Other work information' took about 3.8%. The object scanned by an application is linked with other information, which is similar to conventional web art. As a result, Augmented Reality was the most prominent art pieces made in the realm of Modern App Art. This form of expression was exclusive to the genre App Art and was not found in other genres of Digital Art. Further, more in-depth, and varied discussions are expected to continue regarding this significance of such difference. Furthermore, this research helped expand the scope of the unmarked territory that is the genre of Modern App Art.